Value chain analysis of malt barley in North western part of Ethiopia - Metadel Kassaw; Akalu Teshome; Essa Chanie; Yonnas Addis (Cogent Social Sciences, 2021)
This research attempted to analyze value chain of Malt barley in North Western part of Ethiopia in Estie District. The primary data were collected from 121 malt barley producer farmers selected through two stage sampling technique and from other respective actors. To analyze the data, both descriptive and econometric analytical tools were applied. From Malt barley value chain actors, the chain is governed mainly by malt factory with the assistance of primary cooperatives and cooperative union. From three market channels, channel three product passes from produces to malt factory through primary cooperatives and union is the major marketing channel for malt barley product. The highest gross marketing margin (62.9%) was shared by malt factory, but the profit margin was highest for producers (53.4%). Multiple linear regression model results show that six variables such as education level of the household, farming experiences in malt barley production, choice of contract agreement, availability of active labor force, credit access and land allocated to malt barley production significantly and positively affect the quantity supply of malt barley product. The results of the study, therefore, suggested that policy implications drawn from the study findings include the need to improve the input supply such as improved seed, improving farmers’ knowledge and experience on malt barley production, encouraging adult education, expanding accessibility of credit and improve market infrastructure.